Wideband Absorbance in Ears with Retraction Pockets and Cholesteatomas: A Preliminary Study - Aithal, Sreedevi; Aithal, Venkatesh; Kei, Joseph; Anderson, Shane (Journal of the American Academy of Audiology, 2020)
Objectives The objective of this study was to describe wideband absorbance (WBA) findings in patients with cholesteatomas and retraction pockets (RPs).Design In this prospective study, tympanometry, audiometry, and wideband tympanometry (WBT) were performed on 27 ears with an RP (eight with epitympanic RP and 19 ears with mesotympanic RP), 39 ears with a cholesteatoma (23 ears with epitympanic and 16 ears with mesotympanic cholesteatomas [MCs]), and 49 healthy ears serving as controls.Results Mean WBA at ambient pressure (WBAamb) of both experimental groups was reduced significantly between 0.8 and 5 kHz relative to the control group. The difference between mean WBAamb and mean WBA at tympanometric peak pressure (WBATPP) was greater for the RP (0.12–0.16 between 0.5 and 1.5 kHz) than for the cholesteatoma group (0.03–0.11 between 0.6 and 3 kHz). Mean WBAamb of both epitympanic RP (ERP) and epitympanic cholesteatoma (EC) subgroups was significantly lower than that of the control group. Mean WBATPP of the ERP subgroup attained normal levels as per the control group, while mean WBATPP of EC subgroup was significantly lower than that of the control group at 0.8 to 1.5 kHz and 4 to 5 kHz. In contrast, both mesotympanic RP and MC subgroups demonstrated similar mean WBAamb and WBATPP values. No significant differences in WBAamb and WBATPP results between the RP and cholesteatomas groups were observed. Receiver operating characteristic (ROC) analyses indicated that the area under the ROC curve for distinguishing between the RP and cholesteatomas groups ranged from 0.44 to 0.60, indicating low accuracy in separating the two groups.Conclusion While it is not possible to distinguish between the RP and cholesteatomas groups based on the WBAamb and WBATPP results, it is potentially feasible to differentiate between the EC and ERP conditions. Further study using a large clinical sample is recommended to determine the sensitivity and specificity of the WBA test to identify the EC and ERP conditions.
Keywords: wideband absorbance; wideband tympanometry; cholesteatoma; retraction pockets; conductive hearing loss